Comments summarization - Adilkhanov, Bauyrzhan (2014)
The abundance of social media platforms and other traditional types of websites allowing their users to communicate via comments as well as the availability and spread of various comment hosting services resulted in a lot of information being generated every day in a form of comments. Comments are generally short written remarks expressing someone’s opinions or reactions on a particular topic.